Representation of Different Types of Adjectival Polysemy in the Mental Lexicon - Apresjan, Valentina; Lopukhina, Anastasiya; Zarifyan, Maria (Frontiers in Psychology, 2021)
We studied mental representations of literal, metonymically different, and metaphorical senses in Russian adjectives. Previous studies suggested that in polysemous words, metonymic senses, being more sense-related, were stored together with literal senses, whereas more distant metaphorical senses had separate representations. We hypothesized that metonymy may be heterogeneous with respect to its mental storage. ‘Whole-part’ metonymy (‘sad person’ - ‘sad eyes’), which is cognitively closer to the literal sense and more regular, should be stored differently from temporal, causal or resultative metonymy (‘sad person’ – ‘sad time’; ‘sad person’ - ‘sad news’; ‘lead.ADJ ball’ - ‘lead.ADJ poisoning’), which is irregular and semantically distant from the literal sense. We conducted an online experiment with semantic clustering task in which the participants were asked to classify sentences with a literal, proximal metonymic, distal metonymic, or metaphorical sense of an adjective into virtual baskets so that sentences with the same perceived sense were put in the same basket. Our results showed that proximal metonymies were grouped together with the literal sense and with each other more often than with distal metonymies and metaphors. Distal metonymies, in turn, were grouped with literal senses more often than with metaphors. Overall, we concluded that literal senses and proximal metonymies were stored in single representations, distal metonymies formed hybrid representations with literal senses, and metaphors were stored separately from literal senses. Additionally, we discovered that perception of semantic differences is affected by the surrounding senses: distal metonymies were more discernible from literal senses when presented with proximal metonymies, and less so when presented with metaphors.